Respuestas

¡La mejor respuesta!
2012-07-18T19:40:50+02:00

1..

 

1 + 1 = 1

7     x    5


1(x)+ 1(7) = 1

     7(x)          5


 x+7   =  1

  7x         5


5(x+7) = 7x(1)

5x+35 = 7x

      35 = 7x - 5x 

      35 = 2x 

      35/2 = x

    <> 17,5= x


2..


2(x-3) = x-3

     5         8


2x-6 = x-3

   5        8


8(2x-6) = 5(x-3)

16x-48 = 5x-15

16x-5x = -15+48

     11x = 33

         x = 33/11

        x = 3


*Espero haberte ayudado, saludos.



2012-07-18T19:41:07+02:00

1/7+1/x=1/5  multiplico la ecuacion por x      x/7 + 1 = x/5

x/7 - x/5 = -1

(5x-7x)/35 = -1

-2x = -35

x = 35/2

 

 

2(x-3)/5=x-3/8   ......  2(x-3)/5 = (8x-3)/8

(8)(2)(x-3) = (8x-3)(5)

16x-48 = 40x -15

16x-40x = 48-15

-24x= 33

x=33/(-24) = -(33/24)